2012
DOI: 10.1103/physrevd.86.064041
|View full text |Cite
|
Sign up to set email alerts
|

No-go on strictly stationary spacetimes in four/higher dimensions

Abstract: We show that strictly stationary spacetimes cannot have nontrivial configurations of form fields/ complex scalar fields. This means that the spacetime should be exactly Minkowski or anti-deSitter spacetime depending on the presence of negative cosmological constant. That is, self-gravitating complex scalar fields and form fields cannot exist.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
47
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 30 publications
3
47
0
Order By: Relevance
“…It happens that strictly stationary Einstein-Maxwell spacetime with negative cosmological constant does not allow for the existence of nontrivial configurations of complex scalar fields or form fields [54]. The same situation takes place in the case of strictly stationary, simply connected Einstein-Maxwell-axion-dilaton spacetime with negative cosmological constant and arbitrary number of {/(l)-gauge fields [55].…”
Section: Introductionmentioning
confidence: 98%
“…It happens that strictly stationary Einstein-Maxwell spacetime with negative cosmological constant does not allow for the existence of nontrivial configurations of complex scalar fields or form fields [54]. The same situation takes place in the case of strictly stationary, simply connected Einstein-Maxwell-axion-dilaton spacetime with negative cosmological constant and arbitrary number of {/(l)-gauge fields [55].…”
Section: Introductionmentioning
confidence: 98%
“…In Ref. [7] it was shown that strictly stationary AdS spacetime cannot allow for the existence of nontrivial configurations of complex scalar fields or form fields. The generalization of the aforementioned problem, i.e., strict stationarity of spacetimes with complex scalar fields in Einstein-Maxwell-axion-dilaton gravity with a negative cosmological constant, was given in [8].…”
Section: Introductionmentioning
confidence: 99%
“…Classical results in GR established the inexistence of gravitating solitons in vacuum [26,27], electrovacuum [28], or AdS vacuum [29]. Remarkably, in AdS electrovacuum, and despite apparent obstructions [30], such solitons exist naturally. They were anticipated and constructed linearly in Ref.…”
mentioning
confidence: 99%